Evaluasi Life Cycle Cost Produksi Campuran Aspal Modifikasi Skala Laboratorium - Daniel, Christian Gerald; Firdaus, Fadhil M.; Imanuella , Mazmuria Irene; Firdaus, Fadhil M (Universitas Katolik Parahyangan, 2024)
This paper compares the life cycle costs (LCC) of various asphalt mixture technologies added with polymeric substances that modify either the binder or the whole mix and evaluates the hotspot of each mix type with the scope of cradle-to-gate from the raw materials purchase to the production of 7 kg samples. The polymer-modified binder yields the largest total cost of IDR 12,197, followed by the polymer-modified warm and hot asphalt mixture with a difference of up to 3% and 14.5%, and the standard hot mix gives the lowest result (IDR 9,344) of 23.4% smaller than the largest. Raw material price holds the major contribution with approximately 82.7%, while electricity consumption accounts for 30%. Oven heating contributes the most to the calculated impact from the lab production by 40 to 60%, followed by the mixing activity by a 10 – 30% difference. Conclusively, the LCC of bituminous mixture production is heavily influenced by raw materials price and electricity consumption, and the standard hot mix asphalt generates the lowest total cost, despite having a higher cost than the warm mix in the production stage.